PERBANYAKAN DAN PEMANFAATAN TANAMAN HIAS OBAT DAN UPACARA UNTUK PELUANG WIRAUSAHA MASYARAKAT DESA JUNGUTAN KARANGASEM BALI - Defiani, M.R.; Astarini, I.A.; Wijaya, I.M.S.; Kriswiyanti, E.; Sukmaningsih K, A.A.S.A.; Gunam, I.B.W. (Buletin Udayana Mengabdi, 2023)
Community service for PKK members and youth organizations at the Samsara Living Museum, Jungutan Village, Karangasem, Bali aimed to assist preserve ceremonial plants which include ornamental plants and coconuts of various types and the introduction of blue tea from Clitoria ternatea and turmeric drink for the use of medicinal plants. The initial method was carried out with a site survey to take an inventory of plants at the service location, then socialization with participants was carried out through poster presentations and then continued with the practice of plant nurseries and making blue tea and taste testing of herbal turmeric and tamarind drink. Based on the results of the implementation in the field, most of the participants were new to the existence of blue tea which is beneficial for health because it contains antioxidants. The vegetative propagation of ornamental plants with high economic value such as aglonema, Sanseviera and red betel was very interesting for the participants to increase the effort of propagation of ornamental plants that could be done easily. The introduction of some coconuts such as Mulung coconut which can be used to maintain the body's immunity during a pandemic. The turmeric and tamarind drink helps stamina during the pandemic and can also be tried by participants and has been used as a 'welcome drink' for visitors to Samsara. Some PKK members have tried to grow eggplant and chili vegetables in their yard and are interested in increasing ornamental plants for entrepreneurial activities to motivate other PKK members. Keywords: cutting, grafting, seed, tuber, community empowerment